2011
DOI: 10.1016/j.jss.2009.09.021
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin Expression in Cold Preserved Kidneys in University of Wisconsin and Histidine-Tryptophan-Ketoglutarate Solutions

Abstract: The differences and efficacy of standard preservation solutions in kidney transplantation, University of Wisconsin (UW) and histidine-tryptophan-ketoglutarate (HTK), remain a topic of debate in recent clinical studies. P-selectins represent glycoproteins expressed on endothelial cells and platelets responsible for the earliest events in ischemia/reperfusion injury in kidney transplantation. This study aimed to compare the levels of P-selectin expression between cold preserved kidney tissues in UW and HTK solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…In our study, 24 h of cold storage revealed tubular damage in renal grafts, which is in accordance with the findings by Worku et al [21]. The magnitude of the tubular damage was more pronounced when grafts were stored in HTK.…”
Section: Solutions University Of Wisconsin (Uw) Solution Andsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, 24 h of cold storage revealed tubular damage in renal grafts, which is in accordance with the findings by Worku et al [21]. The magnitude of the tubular damage was more pronounced when grafts were stored in HTK.…”
Section: Solutions University Of Wisconsin (Uw) Solution Andsupporting
confidence: 93%
“…Also, in experimental transplantation, the efficacy of the differing solutions remains a matter of debate, as some studies reported comparable efficacy whereas UW solution was found to be superior in others [20][21][22]. The present study was conducted to compare HTK and UW with regard to cooling properties of solutions, early graft function, tubular damage, and animal survival after renal transplantation.…”
Section: Introductionmentioning
confidence: 98%
“…The influence of OPS on the expression of adhesion molecules could provide additional information in relation to recruitment of immune cells in inflammation during organ reperfusion. Comparative studies of HTK and UW solutions have shown much lower expression of P-selectin in the UW solution group, which demonstrates a significant benefit over HTK [46]. …”
Section: Ischemia/reperfusion Injury As a Major Focus In Organ Presermentioning
confidence: 99%
“…The immersion cooling preservation method is now commonly used in clinical practice because of the simplicity of the procedure and transportation. The permissible ischemia time before restarting blood flow once the organ has been harvested from the donor is 4 h for the heart 1 , 8 h for the lungs 2 , 12 h for the liver and small intestine 3 , 4 , and 24 h for the pancreas and kidneys 5 , 6 . Organ transplants from marginal donors, such as cardiac arrest donors or elderly donors, have gradually become mainstream in the recent years to increase the number of donor organs.…”
Section: Introductionmentioning
confidence: 99%